Nobody's perfect. - Hogge, Becky (New Statesman, 2007)
In this article the author discusses issues arising from the design and development of computer software. The practice of developing and launching updated versions of basic software is examined. She argues against the neo-Luddite notion that advances in computer design and function are dehumanizing elements.